Синтез и структура сегментированных полиэфируретанов на основе смеси полиэдральных олигосилсесквиоксанов - Гомза, Ю.П.; Близнюк, В.Н.; Гуменная, М.А.; Шевчук, А.В.; Клименко, Н.С.; Шевченко, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
We have synthesized the nanostructured poly(ether urethane)s of cross-linked and branched topology by using a mixture of polyhedral oligomeric silsesquioxanes (POSS-M) containing tertiary amine and primary and secondary hydroxyl groups in the organic part of molecules. These compounds are characterized by methods of IR spectroscopy, gel permeation chromatography (GPC), atomic force microscopy (AFM), and small angle X-ray scattering. The structure of the materials is characterized by nanosized clusters enriched with the inorganic phase forming a paracrystalline macrolattice with hexagonal symmetry. The sizes of clusters, contents of the inorganic phase in them, and the value of macrolattice periodicity are determined by the topology of synthesized poly(ether urethane)s.